Mafalda : A Social and Political History of Latin America's Global Comic - Cosse, Isabella (Book collections on Project MUSE., 2019)
In Mafalda: A Social and Political History of Latin America's Global Comic Isabella Cosse examines the history, political commentary, and influence of the world-famous comic character Mafalda from her Argentine origins in 1964 to her global reach in the 1990s.